2001
DOI: 10.1046/j.1365-3156.2001.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in Blantyre, Malawi 1994–1998

Abstract: SummaryIn this paper, we report the ®rst results from the population-based cancer registry for Blantyre district, Malawi, for the period 1994±1998. In this 5-year period, 1245 cases were recorded in males (an estimated age-standardized incidence of 92.0 per 100,000) and 1003 in females (an age standardised rate (ASR) 1 of 88.8 per 10 5 ). The overall percentage of cases with histological veri®cation was just 41.8%, indicating that case-®nding outside the laboratory had been quite successful; nevertheless the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 30 publications
(31 reference statements)
1
37
0
1
Order By: Relevance
“…2,[11][12] As in other studies [1][2][3][4][5][6]14 late presentations with advanced disease compounded by delays in establishing a diagnosis and starting treatment were also problems encountered in management in this study.…”
Section: Discussionsupporting
confidence: 58%
“…2,[11][12] As in other studies [1][2][3][4][5][6]14 late presentations with advanced disease compounded by delays in establishing a diagnosis and starting treatment were also problems encountered in management in this study.…”
Section: Discussionsupporting
confidence: 58%
“…This is similar to what was reported in Zambia [23], using data from histopathological records of the University Teaching Hospital, which was the national referral center, where 32.5% and 19% of all cases diagnosed in 1990–1992 were lymphomas and Kaposi sarcomas, respectively. Similarly, lymphomas accounted for more than half of the diagnosis in Blantyre, Malawi, during 1991 and 1998 [24]. Data from the Harare Cancer Registry for 1993–1995, in Zimbabwe, showed that leukaemia, Wilms tumor, and retinoblastoma accounted for 15.1%, 14.4%, and 11.0% of the diagnoses, respectively, and that Kaposi sarcoma and lymphomas accounted for 10.3% and 8.2% of the diagnoses, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…The 50 articles considered irrelevant did not comply with the exclusion/inclusion criteria set for this review; however, some were retained for extra information, mainly in the discussion. The 15 relevant articles [10,20,[32][33][34][35][36][37][38][39][40][41][42] were then supplemented by the 21 data sets secured with permission from the IARC [43,44] and the further 21 data sets which were received from the directors of the cancer registries through the IACR [16]. Six articles, which were not suitable for contribution to the estimates of incidence but were sourced for full-text copies, were retained for information on the biological characteristics of CRC diagnosed in SSA.…”
Section: Search Strategy For Systematic Analysis and Data Extractionmentioning
confidence: 99%